The effect of resistance exercise on strength and safety outcome for people with haemophilia: A systematic review. Issue 2 (24th February 2020) - Wagner, Barbara; Krüger, Steffen; Hilberg, Thomas; Ay, Cihan; Hasenoehrl, Timothy; Huber, Dominikus Franz‐Xaver; Crevenna, Richard
Abstract: Introduction: Haemophilia is a congenital bleeding disorder with severe musculoskeletal complications. Resistance exercise is important to increase joint stability and to improve physical performance. Aim: This review aimed to investigate the safety and efficacy of resistance exercise interventions on people with haemophilia (PwH) and evaluate whether the American College of Sports Medicine resistance exercise criteria for healthy adults are valid for this population. Methods: A systematic search in literature was conducted, using the databases PubMed, MEDLiNE, CINAHL, SCOPUS, PEDro and Cochrane Library. Out of 2.440 studies published between 1960 and November 2019, 14 studies (9 randomized controlled trials, 1 controlled trial, 4 single‐group prospective studies) applying resistance exercise in juvenile and adult PwH corresponded to the inclusion criteria. Results: Studies performed dynamic, isokinetic or a combination of isometric and dynamic resistance training. Most interventions were carried out in the context of a multimodal training. Resistance was provided using fixed and free weights, body weight, resistance bands and water resistance. Study protocols included clinical and home‐based settings. Several studies suggest that training intensities lower than those known to increase the strength of healthy people are effective in increasing the strength of PwH. Resistance exercise seems to be a safe intervention if it is adequately monitored, individually adapted and applied with sufficient factor therapy. Due to the heterogeneity of study designs, training interventions and outcome measures a meta‐analysis could not be performed. Conclusions: Further studies of higher methodological quality are needed to determine the optimal types of exercise, optimal dosage and timing.